PENGARUH BELANJA PEMERINTAH DAN PAD TERHADAP PDRB TAHUN 2014-2022 DI KOTA SURABAYA - Erwin Putra Rasul Dafana; Arga Christian Sitohang (widya balina, 2025)
This study aims to analyze the effect of government expenditure and Regional Own-Source Revenue (PAD) on the Gross Regional Domestic Product (GRDP) of Surabaya City during the period 2014–2022. The background of the study stems from the crucial role of regional fiscal policy in promoting economic growth and the observed mismatch between the increase in regional expenditure and PAD with the development of GRDP. The research employs a quantitative approach using multiple linear regression analysis based on time-series data obtained from BPS and DJPK. The findings show that government expenditure and PAD simultaneously have a significant effect on GRDP. Partially, government expenditure has a positive and significant effect, while PAD has a positive but not significant effect on GRDP. The coefficient of determination (R²) value of 0.998 indicates that both variables can explain most of the variation in GRDP. These results confirm that government expenditure is the dominant fiscal instrument in driving economic growth in Surabaya, while the contribution of PAD still needs to be strengthened to effectively enhance fiscal capacity and stimulate productive economic activities. This study is expected to serve as a reference for local governments in formulating more targeted budget policies